2016
DOI: 10.3920/bm2015.0083
|View full text |Cite
|
Sign up to set email alerts
|

Anti-obesity effect of milk fermented by Lactobacillus plantarum NCDC 625 alone and in combination with herbs on high fat diet fed C57BL/6J mice

Abstract: The effect of dietary supplementation of milk fermented with indigenous probiotic Lactobacillus plantarum (LP625) alone and in combination with herbs (Aloe vera and Gymnema sylvestre) was investigated on high fat diet (HFD, 60 kcal% fat) fed mice for 12 weeks. Administration of LP625 alone or in combination with both herbs lowered the final body weight, however, a significant difference was observed with LP625 supplemented Gymnema sylvestre only as compared to the HFD fed group (25.06±0.18 vs 27.29±0.72 g, P<0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 44 publications
1
17
0
1
Order By: Relevance
“…Several strains of Lactobacillus plantarum have been identified in multiple studies as having anti-obesity effects [7,8,38,39,40,41]. Data from our research study revealed a L. plantarum gene for the universal stress protein that is in operon association with a gene for fatty acid oxidation.…”
Section: Discussionmentioning
confidence: 60%
“…Several strains of Lactobacillus plantarum have been identified in multiple studies as having anti-obesity effects [7,8,38,39,40,41]. Data from our research study revealed a L. plantarum gene for the universal stress protein that is in operon association with a gene for fatty acid oxidation.…”
Section: Discussionmentioning
confidence: 60%
“…Furthermore, the findings of the mentioned study were indicative of the protective effects of both products against the rise in the serum and hepatic TG, as well as in the hepatic TC level. Moreover, LP625 in combination with both herbs could protect against diet‐induced obesity through decreasing epididymal fat weight and expression of proinflammatory cytokines, as well as increasing the relative mRNA expression of thermogenic proteins (i.e., uncoupling protein‐2 [UCP‐2]; Pothuraju et al, ).…”
Section: Antiobesity Effectsmentioning
confidence: 99%
“…Importantly, at the strain level of L. plantarum , the anti‐obesity effects were observed in the strains LG42, TN8 and No.14, but those were not found in the strains OLL2712, KY1032, and WCSF1, indicating that the probiotic effect is strain‐dependent . Recently, especially from 2015 to July 2018, more and more species or strains of Lactobacillus and Bifidobacterium were showed to have potential for anti‐obesity, such as L. rhamnosus NCDC 17 (LR17), L. casei Shirota, L. rhamnosus PB01 (DSM 14870), L. sakei OK67, L. plantarum Q180, L. plantarum NCDC 625 (LP625), L. acidophilus AD031, B. bifidum BGN4, B. longum BORI, L. mali APS1, L. kefiri DH5, and L. plantarum Ln4 . According to the FAO/WHO definition of probiotics, we summarized the information of the newly discovered anti‐obesity probiotics in Table , especially in the aspect of their experimental models and anti‐obesity effects, to examine: (a) the adequate amounts; (b) the administration conditions; (c) the ability to colonize or survive in the gut; and (d) the anti‐obesity effects of these microbes.…”
Section: Microbiome‐based Anti‐obesity Potential: Next‐generation Promentioning
confidence: 99%
“…While a numerous of experimental models have been used, the divergence in administrating conditions, such as the differences in resuspension solution, obese models and the host animals may lead to diverse results and conclusions. For example, while the PBS or normal saline were generally used for dilution of probiotics, some studies used the skim milk for resuspension or generation of fermented milk (Table ). It is required to test whether the anti‐obesity outcome is resulted from the probiotics' nature or other beneficial components, such as the metabolites of probiotics or the materials of resuspension solution.…”
Section: Microbiome‐based Anti‐obesity Potential: Next‐generation Promentioning
confidence: 99%
See 1 more Smart Citation